EVALUATION OF DNA BARCODING METHODOLOGY AND SUBSTITUTION PREVAILING IN “SANDLEWOOD” HERBAL TRADE MARKET - Sharma, Tina; Thakar, Mukesh Kumar (Journal of Forensic Medicine and Toxicology, 2019)
Indian red sandalwood (Pterocarpus santalinus) is a valuable forest produce which is used as an anti hyperglycaemic and diaphoretic drug. Surplus demand of red sandalwood by herbal industry has led to the over exploitation of the species in the wild. The illegal trafficking often confiscated by the police department needs a validated tool to identify plants in illegal trade. Controlling measures of international trade has is hampered by the inability to identify plant samples to the species level. Therefore, the present study evaluated the potential of molecular identification by searching for species-specific DNA polymorphisms. Our DNA barcoding method was tested for its specificity, reproducibility, sensitivity and stability. The study includes samples of wood tissues and herbal outlet samples, which had been treated differently for preservation. DNA extractions were tested in a range of amplification settings and dilutions. Species-specific sequences were obtained from matk, rbcl and ITS gene marker were submitted in NCBI gene bank. Our results demonstrate that molecular analysis provides new perspectives for forensic identification of Indian red sandalwood
Keywords: Red sandalwood; wildlife forensic; DNA barcoding; Illegal Trade; Forensic science